2014
DOI: 10.1128/jcm.02738-13
|View full text |Cite
|
Sign up to set email alerts
|

Free-Living Amoebae Recovered from Human Stool Samples in Strongyloides Agar Culture

Abstract: Our laboratory in The Gambia, West Africa, performs Koga agar (1.5% bacteriological agar, 0.5% sodium chloride, 0.5% meat extract, 0.1% bacteriological peptone) culture for larvae of strongyle nematodes on human fecal samples for which parasitological investigation has been requested. We have recovered freeliving amoebae (FLA) from human fecal specimens on two occasions over a period of 9 months (representing 130 individual fecal cultures) on this agar (Fig. 1). The amoebae in both cases were identified as Har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 11 publications
2
18
0
1
Order By: Relevance
“…In previous studies, similar results were reported [1,29], and this further justified the use of V. vermiformis for the co-culture experiments. Moreover, the recent isolation of Hartmannella species from the stools of Humans reinforced their role as Trojan horses for the transmission of pathogens [36]. Finally, recently, Kebbi-Beghdadi proposed that coculture using Acanthamoeba sp.…”
Section: Discussionmentioning
confidence: 97%
“…In previous studies, similar results were reported [1,29], and this further justified the use of V. vermiformis for the co-culture experiments. Moreover, the recent isolation of Hartmannella species from the stools of Humans reinforced their role as Trojan horses for the transmission of pathogens [36]. Finally, recently, Kebbi-Beghdadi proposed that coculture using Acanthamoeba sp.…”
Section: Discussionmentioning
confidence: 97%
“…(Table 1 ; Figures 1 – 5 ; Reteno et al, 2015 ). The recovery of this virus from a sewage sample collected in Marseille, France, resulted from the implementation of a high-throughput strategy to isolate new giant viruses from environmental samples that included the use of five other protists, in addition to those from the genus Acanthamoeba , including Vermamoeba vermiformis , which appeared as the most common free-living protist in human environments (Bradbury, 2014 ). Faustovirus E12 was the prototype isolate to be described, then seven additional faustovirus isolates were recovered and their genomes sequenced (Reteno et al, 2015 ).…”
Section: Faustovirusesmentioning
confidence: 99%
“… 2005 ). In addition to FLA being present in water systems, they have been identified within the gastrointestinal track of humans from the stomach to faeces (Thamprasert, Khunamornpong and Morakote 1993 ; Bradbury 2014 ), they are considered as an amphizoic organisms and live as parasites within host tissue (ability to live endozoically) (Page 1967 ; Jadin 1973 ; Martinez and Visvesvara 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…The selected FLA are, W. magna belonging to the Vahlkampfiidae family and Vermamoeba vermiformis , belonging to Vermamoebidae family and one of the most common free-living protists in human environments (de Moura et al . 1985 ; Bradbury 2014 ; Delafont et al . 2018 ).…”
Section: Introductionmentioning
confidence: 99%